2023
DOI: 10.3389/fmicb.2023.1179953
|View full text |Cite|
|
Sign up to set email alerts
|

Probiotic characteristics and whole-genome sequence analysis of Pediococcus acidilactici isolated from the feces of adult beagles

Abstract: The beneficial effects of lactic acid bacteria are well known and recognized as functional foods that are health benefits for companion animals. This study, for the first time, reports the probiotic properties, safety, and whole-genome sequence of Pediococcus acidilactici GLP06 isolated from feces of beagles. In this study, candidate probiotic bacteria P. acidilactici GLP02 and GLP06 were morphologically characterized and tested for their antimicrobial capacity, tolerance to different conditions (low pH, bile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that P. acidilactici can improve host gut microbiota, stimulate various non-specific immunities, and inhibit the growth of pathogenic bacteria in the gut intestinal tract ( Ferguson et al, 2010 ; Fernandez et al, 2016 ; Kim et al, 2018 ; Zhang et al, 2022 ). Regarding P. acidilactici GLP06, our previous study has shown that canine-derived P. acidilactici GLP06 has probiotic potential and antioxidant capacity and is safe and free of drug-resistance genes ( Zhao et al, 2023 ). In this study, neither ATTD nor nitrogen metabolism was significantly altered in beagles fed with P. acidilactici GLP06.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that P. acidilactici can improve host gut microbiota, stimulate various non-specific immunities, and inhibit the growth of pathogenic bacteria in the gut intestinal tract ( Ferguson et al, 2010 ; Fernandez et al, 2016 ; Kim et al, 2018 ; Zhang et al, 2022 ). Regarding P. acidilactici GLP06, our previous study has shown that canine-derived P. acidilactici GLP06 has probiotic potential and antioxidant capacity and is safe and free of drug-resistance genes ( Zhao et al, 2023 ). In this study, neither ATTD nor nitrogen metabolism was significantly altered in beagles fed with P. acidilactici GLP06.…”
Section: Discussionmentioning
confidence: 99%
“…P. acidilactici GLP06, used in this study, was isolated from the gastrointestinal tract of healthy beagles and completed the probiotic potential and safety evaluation in our laboratory ( Zhao et al, 2023 ). It was kept in the China Centre for Type Culture Collection (CCTCC; Wuhan, China) under the accession number CCTCC No.…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic susceptibility was classified as sensitive (≥ 21 mm), intermediate (16-20 mm), or resistant (≤15 mm). [52]…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%
“…Currently, the integration of whole-genome sequencing and bioinformatics could comprehensively explore the genetic and biological characteristics of strains with enhanced resolution and sensitivity. This approach provides valuable insights into various aspects such as genetic information, evolutionary relationships, physiological traits, probiotic potential, safety profiles, among others [14]. However, it is crucial to acknowledge that phenotypic analysis remains indispensable for probiotic discovery due to potential errors in the sequencing process and limited concordance between genomic sequences and existing databases [15].…”
Section: Introductionmentioning
confidence: 99%